Vesicular Stomatitis Virus-Vectored Multi-Antigen Tuberculosis Vaccine Limits Bacterial Proliferation in Mice following a Single Intranasal Dose - Zhang, Ming; Dong, Chunsheng; Xiong, Sidong (Frontiers in Cellular and Infection Microbiology, 2017)
Tuberculosis (TB) remains a serious health problem worldwide, and an urgent need exists to improve or replace the available vaccine, Mycobacterium bovis bacillus Calmette-Guérin (BCG). Most vaccination protocols adapt two or three doses to induce long-term lasting immunity. Our previous study showed that the naked DNA encoding the triple-antigen fusion TFP846 (Rv3615c-Mtb10.4-Rv2660c) induced robust T cellular immune responses accompanying four inoculations against mycobacteria infection. However, a number of compliance issues exist in some areas lacking the appropriate medical infrastructure with multiple administrations. In this study, a novel vesicular stomatitis virus expressing TFP846 (VSV-846) was developed and the immune responses elicited by VSV-846 were evaluated. We observed that intranasal delivery of VSV-846 induced a potent antigen-specific T cell response following a single dose and VSV-846 efficiently controlled bacterial growth to levels 10-fold lower than that observed in the mock group 6 weeks post-infection in BCG-infected mice. Importantly, mice immunized with VSV-846 provided long-term protection against mycobacteria infection compared with those receiving p846 or BCG immunization. Increased memory T cells were also observed in the spleens of VSV-846-vaccinated mice, which could be a potential mechanism associated with long-term protective immune response. These findings supported the use of VSV as an antigen delivery vector with the potential for TB vaccine development.